ATR/Chk1 signaling induces autophagy through sumoylated RhoB-mediated lysosomal translocation of TSC2 after DNA damage. Issue 1 (December 2018) - Liu, Mingdong; Zeng, Taoling; Zhang, Xin; Liu, Chunyan; Wu, Zhihui; Yao, Luming; Xie, Changchuan; Xia, Hui; Lin, Qi; Xie, Liping; Zhou, Dawang; Deng, Xianming; et al.
Abstract DNA damage can induce autophagy; however, the underlying mechanism remains largely unknown. Here we report that DNA damage leads to autophagy through ATR/Chk1/RhoB-mediated lysosomal recruitment of TSC complex and subsequent mTORC1 inhibition. DNA damage caused by ultraviolet light (UV) or alkylating agent methyl methanesulphonate (MMS) results in phosphorylation of small GTPase RhoB by Chk1. Phosphorylation of RhoB enhances its interaction with the TSC2, and promotes its sumoylation by PIAS1, which is required for RhoB/TSC complex to translocate to lysosomes. As a result, mTORC1 is inhibited, and autophagy is activated. Knockout ofRhoB severely attenuates lysosomal translocation of TSC complex and the DNA damage-induced autophagy. Reintroducing wild-type but not sumoylation-resistant RhoB intoRhoB −/ − cells restores the onset of autophagy. Hence, our study identifies a molecular mechanism for translocation of TSC complex to lysosomes in response to DNA damage, which depends on ATR/Chk1-mediated RhoB phosphorylation and sumoylation. DNA damage can lead to autophagy. Here the authors reveal a molecular mechanism for ATR/Chk1 signaling-induced autophagy in response to DNA damage, through an ATR/Chk1/RhoB-mediated lysosomal recruitment of TSC complex and subsequent mTORC1 inhibition.